PHYTOCHEMICAL PROFILING OF SOLANUM NIGRUM AND SOLANUM SURATTENSE FROM LOCAL AREA OF DALA AND GWALE, NIGERIA - H., HARUNA; S.P., BAKO, Y., MUSTAPHA; A.A., ALIKO (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
An investigation of phytochemical analysis of some members of the family solanaceae was carried out at the Department of Biological Sciences, Bayero University Kano. The result of the phytochemical screening of members of the Solanaceae family showed the presence of phytochemicals such as, Tannins, steroids, resins, alkaloids saponins, reducing sugars and flavonoids in both species of Solanum nigrum and Solanum surattense studied. The results of Thin Layer Chromatography showed similarities at Rf values 0.62, 0.78 and 0.90 while differences were found at R f values 0.50, 0.66, 0.96 and 0.65.The result of HPLC phytochemical profiling showed similarities as well as differences. Similarities between Solanum surattense were at the retention time 31 minutes after elution while differences in retention time peaks were found at 15, 19, 21, 23, 33, 39, 38 and 48 minutes at (254nm). Also at 360nm there was also similarity at 31 and 39 minutes after elution and differences at 18, 19, 33, 37, 40 and 43 minutes. Confirmation of the presence of ellagic Acid at retention time 31 minutes in both Solanum nigrum and Solanum surattense and differences at 15 minutes showed catechol in Solanum nigrum and also Tannic acid at retention time 33 minutes at (254nm). At retention time 39 minutes Acety-Salicylic acid was confirmed in Solanum surattense. Difference was also found in Solanum nigrum at retention time 41 minutes and was confirmed to be Benzoic acid. This research therefore, proved that plant species belonging to the family Solanaceae contain different types of phytochemicals and thus could be utilize as a tool for modern classification.